Factors determining Islamic Banks' deposits in Qatar: An empirical study - Abd Aziz, Hassanuddeen; Musse, Osman Sayid Hassan; Echchabi, Abdelghani (International Journal of Economic Practices and Theories, 2014)
The main purpose of the study is to investigate the variables that influence the Islamic banks deposits’ in Qatar in the long- and short runs. The study uses quarterly data covering the period from 2006 through 2013, and applies JJ cointegration test and vector error correction model (VECM). The findings indicate that Islamic banks’ deposits are not influenced by any of the explanatory variables in the long run. Nevertheless, in the short run, Islamic banks’ deposits in Qatar are influenced by CPI, conventional banks’ deposit rate, as well as Islamic banks’ profit rates. This is one of the early studies addressing the issue of Islamic banks’ deposits in Qatar and their determinants. Key words: Qatar, Islamic banks deposits, Cointegration, Profit Rate, Interest Rate.